IMPLEMENTASI MANAJEMEN PERUBAHAN OLEH KEPALA SEKOLAH: STUDI KASUS PADA SD NEGERI NO 3 KUWUM, KABUPATEN BADUNG - Windari, Ni Putu Sri (Widyadari: Jurnal Pendidikan, 2018)
The research method used is descriptive qualitative research. Data collection is obtained from information, places and activities of principal leadership activities, as well as documents. Techniques of collecting data include in-depth interviews, direct observation, and document records. Data validity test is done by applying source triangulation, and triangulation method. Data analysis techniques in the form of interactive analysis techniques that reduce data, present data, interpret and draw conclusions. Principal of SD Negeri No 3 Kuwum, Mengwi Sub-district, Badung Regency in carrying out his leadership has performed his role and function as an educator, manager, administrator, supervisor, leader, innovator and motivator well. In addition, Principal of SD Negeri No 3 Kuwum, in making decision and policy making involving many parties such as teachers, staff and school committee, conducting continuous guidance, can cooperate and support each other in achieving school goals and always coordinate with existing stakeholders, so that the existing constraints do not interfere with the course of the school program created.